Picturebook! Literature starters for early readers - Dalgleish, Sharon; Dalgleish, Tanya; New South Wales. Department of School Education. Media Production Unit. (Ryde, N.S.W. : Curriculum Directorate, NSW Dept. of School Education, 1993)
Program for use with early readers from kindergarten to year 2 featuring the four books, Tessa snaps snakes, My cat Maisie, Farmer beans and the baby wallaby and Greetings from Sandy Beach.
Book written by Tanya and Sharon Dalgleish. Video produced by Media Production Unit. Storyteller Trish Goddard.
Keywords: Reading (Kindergarten); Reading (Primary)